“You Have to Set the Story You Know Aside”: Constructions of Youth, Adulthood and Senescence in Cinderella Is Dead - Michelle Anya Anjirbag; Vanessa Joosen (Humanities, 2022)
As with other twenty-first-century rewritings of fairytales, Cinderella is Dead by Kalynn Bayron complicates the classic ‘Cinderella’ fairytale narrative popularized by Charles Perrault and the Brothers Grimm for new audiences, queering and race-bending the tale in its decidedly feminist revision of the story. However, as we argue here, the novel also provides an interesting intervention in the construction of age as related to gender for its female protagonists. Drawing on Sylvia Henneberg’s examination of ageist stereotypes in fairytale classics and Susan Pickard’s construction of the figure of the hag, we explore the dialogic between the fairytale revision, traditional fairytale age ideology and the intersection of age and gender in this reinvention of the classic narrative. By focusing on constructions of age, particularly senescence, we demonstrate how complex constructions of older characters might aid in overall depictions of intergenerational relationships, and how these intergenerational relationships in turn reflect historical and cultural impetuses of retelling fairytale narratives.